Recykling a kultura - Kulisz, Marek (Er(r)go. Teoria - Literatura - Kultura, 2007)
Marek Kulisz Recycling and Culture - summary The essay is an attempt to analyze the ways in which it may be possible to talk about recycling in culture. Contrary to recycling, the word culture has a long and complicated history, and it is used nowadays in a number of different meanings. Two of these meanings are taken into consideration here. Expressions such as "recycling of culture" and "culture of recycling" will be comprehensible if the word "culture" is used in its broadest sense, i.e. the one in which anthropologists use it when they speak of the nature-culture opposition. In this context recycling is simply part of culture, because — though recycling is modeled on natural phenomena — it is certainly not a natural process; it is a series of carefully planned activities involving state-of-the-art technology. We cannot, however, talk in a sensible way about recycling in culture if we take the word culture in its narrow sense, as the so-called high culture, because culture understood this way does not produce waste. There are no societies that would be willing to dismiss any of their great artists of the past and consider their works of art as waste.